Dowery deaths - "Sharma, Vinay" (New Delhi, 2007)
This book is about a social problem Dowry Deaths: Legal provisions and Judicial interpretation. The book has dealt with the historical perspective how dowry is a deep-rooted problem of Indian society slowly and steadily how the growth of the social problem took place.
Keywords: Dowry death